Note-Taking Instruction for College Students with Autism Spectrum Disorder. Issue 4 (1st October 2016) - Reed, Deborah K.; Hallett, Abigail; Rimel, Hillary
ABSTRACT: Using a multiple baseline across participants design, this study examines the functional relationship between instruction in note-taking skills and the ability of young adults with autism spectrum disorder to take notes on college lectures. The three participants were enrolled in a program aligned with the Higher Education Opportunity Act (Public Law 110-315) to support students with significant cognitive disabilities in attending community college classes. All had graduated high school on a special diploma status and had mild cognitive disabilities. Despite some variability in performance during baseline (when only the note-taking template was introduced), all three students demonstrated increased performance during intervention when they were taught skills such as distinguishing between subtopics and details, paraphrasing, and using abbreviations and symbols. Participants' improvements were maintained after the intervention instruction stopped. Participant Tau-U effect sizes ranged from 0.67 to 1.00, and the weighted average Tau-U effect size was 0.88 (CI95 = 0.53 to 1.24). The discussion addresses implications for the postsecondary participation of students with autism spectrum disorder as well as possible changes needed in their secondary education.